PIMS (Positioning In Macular hole Surgery) trial – a multicentre interventional comparative randomised controlled clinical trial comparing face-down positioning, with an inactive face-forward position on the outcome of surgery for large macular holes: study protocol for a randomised controlled trial. Issue 1 (December 2015) - Pasu, Saruban; Bunce, Catey; Hooper, Richard; Thomson, Ann; Bainbridge, James
Abstract Background Idiopathic macular holes are an important cause of blindness. They have an annual incidence of 8 per 100, 000 individuals, and prevalence of 0.2 to 3.3 per 1000 individuals with visual impairment. The condition occurs more frequently in adults aged 75 years or older. Macular holes can be repaired by surgery in which the causative tractional forces in the eye are released and a temporary bubble of gas is injected. To promote successful hole closure individuals may be advised to maintain a face-down position for up to 10 days following surgery. The aim of this study is to determine whether advice to position face-down improves the surgical success rate of closure of large (>400 μm) macular holes, and thereby reduces the need for further surgery. Methods/Design This will be a multicentre interventional, comparative randomised controlled clinical trial comparing face-down positioning with face-forward positioning. At the conclusion of standardised surgery across all sites, participants still eligible for inclusion will be allocated randomly 1:1 to 1 of the 2 treatment arms stratified by site, using random permuted blocks of size 4 or 6 in equal proportions. We will recruit 192 participants having surgery for large macular holes (>400 μm); 96 in each of the 2 arms of the study. The primary objective is to determine the impact of face-down positioning on the likelihood of closure of large (≥400 μm) full-thickness macular holes following surgery. Discussion This will be the first multicentre randomised control trial to investigate the value of face-down positioning following macular hole standardised surgery. Trial registration UK CRN:17966 (date of registration 26 November 2014).